Effect of drugs on vitamin B12 levels obtained using the Lactobacillus leichmanii method. Issue 6 (November 1969) - Powell, D. E. B.; Thomas, J. H.; Mandal, A. R.; Dignam, C. T.
Abstract : In 750 consecutive assays of serum vitamin B12 levels using Lactobacillus leichmanii, 25 (3·3%) showed inhibition. A satisfactory history of drug therapy was obtained in 23 cases. Seventeen of these were receiving ampicillin at the time. Two patients showed inhibition while receiving phenoxmethyl penicillin or phenethicillin. A prospective study of 11 patients detected inhibition in seven at varying intervals during ampicillin therapy. It was shown that the vitamin B12 as measured by the radioisotope and Euglena gracilis methods was not affected. Inhibition of L. leichmanii was reproduced in vitro with concentrations of ampicillin corresponding to those obtained in therapy. Benzylpenicillin, streptomycin, and chloramphenicol had no such effect. A prospective study of patients receiving chlorpromazine yielded negative results. Inhibition may occasionally be seen in the absence of any known intake of drugs. Measurement by other methods may be required to distinguish this from vitamin B12 depletion.